Improving Character and Learning Discipline Through the Development of Self-Management in Junior High School Students - Tampubolon, Rhoni Ilham (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service program aims to improve students’ character and learning discipline through the development of self-management skills among students of SMP Swasta Amanah 1 Medan, in order to better prepare them to face future challenges. The main objective of this program is to equip students with the ability to manage their time, emotions, and learning discipline in ways that align with current developments and the demands of the workforce. This activity was motivated by students’ low understanding of the importance of self-management, as well as their limited knowledge of good and proper character and learning discipline. The program was carried out through a series of counseling sessions, training, and mentoring activities involving collaboration between teachers and the PKM team. Self-management is an important factor that must be considered and managed well, as it enables students to organize tasks, manage study time, and maximize productivity. Efforts to provide guidance on self-management to improve character and learning discipline—aimed at enhancing students’ academic achievement—were implemented through this community service program for students at SMP Swasta Amanah 1 Medan. The PKM activities began with observation, group discussions with the principal and the vice principal for curriculum affairs, and counseling sessions. During the question-and-answer session, students appeared enthusiastic to ask questions, and their success in attempting to improve their learning efforts was a key indicator of the program’s achievement.